A Philosophical Examination of the Unique Characteristics and Cultural Identity of the Igbo People - Ignatius Nnaemeka Onwuatuegwu (Pusat Studi Pembangunan dan Pemberdayaan, 2023)
This article explores the intrinsic characteristics of the Igbo people from a philosophical perspective. Drawing on Igbo cosmology and metaphysics, the paper argues that the Igbo possess certain distinctive traits such as communalism, practical intelligence, and a deep sense of spirituality. These traits are embedded in the Igbo worldview and shape their cultural practices and social structures. The article further suggests that an understanding of the Igbo's intrinsic characteristics can deepen intercultural understanding and promote a more equitable and inclusive global society. The writer, therefore employed the hermeneutics methodological approach. This approach involves a critical examination of the beliefs, values, and practices of the Igbo people, and how they relate to their worldview and metaphysics. It also considers the ways in which these intrinsic characteristics shape the social structures and cultural practices of the Igbo people, and how they can contribute to a more equitable and inclusive global society.